PENGARUH KETIDAKPUASAN KONSUMEN, IKLAN PESAING, DAN PERILAKU MENCARI VARIASI TERHADAP PERILAKU PERPINDAHAN MEREK (Survei pada Konsumen PT. Bintanglima Anekawarna Surakarta) - Riawan, Ryan (Universitas Slamet Riyadi, 2019)
This research was conducted on consumers of Zinc Chromate Syncro paint products that have moved from competitors' Zinc Chromate paint products. The number of samples determined was 100 respondents, using the sampling technique non-probability sampling, by means of purposive sampling and accidental sampling. Data collection is done by distributing questionnaires. The method of data analysis is done by multiple linear regression using the SPSS software program. Data has been analyzed to meet the validity test, reliability test, and the classic assumption test. Based on the analysis that has been used, several conclusions are drawn when processing multiple linear regression. This study fulfills the validity, reliability, and is free from multicollinearity, heteroscedasticity, autocorrelation and passes the normality test. The regression equation obtained, the dependent variable that has the most significant value is consumer dissatisfaction. Hypothesis testing using the t test shows that the variables of consumer dissatisfaction, competitor advertisements and the behavior of looking for variations, shows these variables significantly influence the decision of brand displacement. Whereas the f test showed significant < 0.05. This means that consumer dissatisfaction variables (X1), competitor advertisements (X2) and variations seeking behavior (X3), have a positive effect and together have a significant effect on brand switching behavior (Y). The coefficient of determination is obtained by the adjusted R Square value of 53.1%. That is, brand displacement decision variables can be explained by the presence of consumer dissatisfaction variables, competitor advertisements, and variations seeking behavior, while the remaining 46.9% can be influenced by other variables, such as prices, promotions, product attributes and so on.